The Effect of AUDI Technology with Improvement Ration on Productivity of Arab's Hen 2nd Phase - Eudia Christina Wulandari; Angela Nitia Nefasa; Hanny Indrat Wahyuni (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2020)
This study used the AUDI’s technology application with repair rations, aimed at increasing the productivity of Arab’s hens in the 2 nd phase. The repair ration is focused on the addition of calcium minerals. AUDI technology is a combination of water filtering technology with extract beluntas (Pluchea indica L.). The research used seventy two Arab’s hen with homogenous body weight. The study used a completely randomized design with 3 treatments, 6 replications, each replication consisting of 3 chickens. The research was conducted in 6 weeks of treatment. The parameters measured in this study were ration consumption, calcium consumption, hen day production (HDP), eggshell weight, and thickness. The results showed that the use of AUDI technology on rations significantly improved (p <0.05) affected ration consumption, calcium consumption, and increased hen day production (HDP), but did not affect weight, and thickness of an eggshell. Feed intake and calcium consumption significantly influenced by differences in calcium and crude protein in the rations. Based on these results, it was found that the use of AUDI technology was able to shorten the clutch cycle in laying hens so that production still reached 60-70% equivalent with phase I. Weight and thickness of eggshells were not affected by the use of AUDI technology and improved rations because the hens used as subject had reached peak production.